(untitled) (Ustozlar uchun, 2025)
Abstract This article scientifically analyzes the interrelation between religion and art, as well as their role and influence in human spiritual life. It broadly discusses how religious values are expressed through art, the unique characteristics of Islamic art, and the reflection of religious ideas in modern culture. The article is prepared based on the ’Religious Studies Complex 2025–2026’ study guide and contemporary sources